VIDARR: monitoring reactor anti-neutrinos using a plastic scintillator detector in a mobile laboratory. (1st October 2022) - Bridges, K.; Carroll, J.; Coleman, J.; Collins, R.; Dasari, J.; Holt, G.; Lockwood, M.; Metelko, C.; Morgan, A.; Murdoch, M.; Schnellbach, Y.; Tsurin, I.; et al.
Abstract: Technology developed for the T2K electromagnetic calorimeter has been adapted to make a small footprint, reliable, segmented detector to characterise anti-neutrinos emitted by nuclear reactors. The device has been developed and demonstrated by the University of Liverpool and underwent field tests at the Wylfa Magnox Reactor on Anglesey, U.K. It was situated in a 20 ft ISO shipping container, above ground, roughly 60 m from the 1.5 GW th reactor core. Based on the design of the T2K Near Detector ECal, the device detects anti-neutrino events through the distinctive delayed coincidence signal of inverse β -decay interactions using extruded plastic scintillator as the target and detection medium and silicon photomultipliers as the photosensors. The detector is undergoing an upgrade to the VIDARR detector system based on the data and experiences of the field trial for easier deployment and better detection sensitivity.